Atypical Variant of Guillain Barre Syndrome in a Patient with COVID-19 - Lowery, Megan M.; Taimur Malik, Muhammad; Seemiller, Joseph; Tsai, Cynthia S. (Journal of critical care medicine (Universitatea de Medicina si Farmacie din Targu-Mures), 2020)
A rare variant Miller Fisher Syndrome overlap with Guillain Barre Syndrome is described in an adult patient with SARS-COV-2 infection. The clinical course of a 45-year-old immunosuppressed man is summarized as a patient who developed ataxia, ophthalmoplegia, and areflexia after upper respiratory infection symptoms began. A nasopharyngeal swab was positive for COVID-19 polymerase chain reaction. He progressed to acute hypoxemic and hypercapnic respiratory failure requiring intubation and rapidly developed tetraparesis. Magnetic resonance imaging of the spine was consistent with Guillain Barre Syndrome. However, the clinical symptoms, along with positive anti-GQ1B antibodies, were consistent with Miller Fisher Syndrome and Guillain Barre Syndrome overlap. The patient required tracheostomy and had limited improvement in his significant neurological symptoms after several months. The case demonstrates the severe neurological implications, prolonged recovery and implications in the concomitant respiratory failure of COVID-19 patients with neurological symptoms on the spectrum of disorders of Guillain Barre Syndrome.